2000
DOI: 10.1002/1097-0274(200010)38:4<410::aid-ajim6>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among workers exposed to cutting oil mist: Update of previous reports

Abstract: Background Earlier reports of the mortality experience of this cohort of automotive workers followed from 1938 to 1967 who were exposed to cutting oil mist noted an excess of gastrointestinal cancer. The present report describes the mortality experience of these workers followed for mortality through 1980. Methods Cause‐specific standardized mortality ratios were calculated by comparing the observed number of deaths to the expected numbers based on rates for the U.S. male population. Results The SMRs for liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 29 publications
0
29
1
Order By: Relevance
“…27 Recently, an increase in biliary tract malignancies has been associated with cutting-oil mist in auto-industry workers. 28 An analysis of specific occupations or industries associated with an increased incidence of cholangiocarcinoma should be undertaken to explore the possibility that occupational exposure to industrial chemicals may have played a causal role. Furthermore, geographic disparities in mortality from biliary tract malignancies have become more prominent in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…27 Recently, an increase in biliary tract malignancies has been associated with cutting-oil mist in auto-industry workers. 28 An analysis of specific occupations or industries associated with an increased incidence of cholangiocarcinoma should be undertaken to explore the possibility that occupational exposure to industrial chemicals may have played a causal role. Furthermore, geographic disparities in mortality from biliary tract malignancies have become more prominent in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 11.5% of the samples did not meet air quality standards. Long-term exposure to particulate matter may cause asthma, heart disease, laryngeal cancer, bronchial hyper-responsiveness, and lung cancer (Kazerouni et al, 2000;Davidsona et al, 2005;Chen et al, 2007;Buonanno et al, 2011;Wendt et al, 2014). Thus, it is very important to study airborne particulate matter in factories.…”
Section: Introductionmentioning
confidence: 99%
“…As in the case of galvanizing installations, these types of metal industries use metalworking fluids (MWFs), a range of oils and other chemical substances used to cool and/or lubricate metal workpieces when they are being machined, ground, milled, etc., and known to be carcinogens in humans (Savitz 2003). Some occupational studies have found excess of lung cancer mortality among workers exposed to certain types of MWFs and mineral oils (Acquavella et al 1993;DHHS (NIOSH) 1998;Kazerouni et al 2000;Tolbert 1997). Furthermore, one study detected a slightly increased lung cancer mortality rate in United Steel production and founding Bold values indicate significant results and different sectors a ORs were estimated from a multiple logistic regression model that included age, sex, hospital area, tobacco consumption, family history of cancer, area of residence, and occupation b Intersection area between industrial area corresponding to each industrial sector and urban area…”
Section: Resultsmentioning
confidence: 99%